Kompetensi Pedagogik Guru Akidah Akhlak dalam Meningkatkan Hasil Belajar Siswa - Aprilina, Leni; Fridiyanto, Fridiyanto; Armida, Armida (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2023)
The main problem of this research is that the pedagogical competence of teachers of moral beliefs is not optimal in improving student learning outcomes at Madrasah Tsanawiyah Nurul Ikhlas, Sungai Raya Village, Batang Tuaka District. This research uses a qualitative approach. Analysis of the results of research conducted by researchers regarding teacher pedagogical competence in improving student learning outcomes at Madrasah Tsanawiyah Nurul Ikhlas, Sungai Raya Village, Batang Tuaka District, shows that it is quite good, but there are several indicators that are not optimal, such as: teachers only focus on active students, learning less centered on student activity, minimal use of varied and interesting methods and media. Student learning outcomes have quite good knowledge scores but are not good in terms of attitudes.